Innovation in Teaching Islamic Education in the Development of Religious and Nationality Understanding in the Taklim Council - Srinarwati, Dwi Retnani; Zaman, Akhmad Qomaru; Suhartono, Suhartono; Imaniar, Rahmatul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Majelis Taklim is a non-formal Islamic educational institution that has its curriculum, is held regularly and regularly, and is attended by a relatively large number of congregations. In Indonesia, the development of educational institutions of the taklim council type is large or in great demand by pilgrims, especially in big cities where people are thirsty for Islamic education, this study aims to understand and analyze the innovation of Islamic education teaching in developing religious and national understanding in the Al-Maryam Taklim Council of North Jakarta. This field research uses a qualitative descriptive approach and uses triangulation techniques to test the validity of the data. The results of the study concluded that the teaching innovation of Islamic religious education in developing religious and national understanding at the Al-Maryam Taklim Council in North Jakarta by conditioning teaching materials, teaching methods (lecture method accompanied by teaching aids/teaching aids, question and answer method, field trip method, discussion method and practice method), teaching approach, and scientific quality of resource persons. Recommendations to researchers who wish to conduct research again at the Taklim Council to find more in-depth information so that our science continues to develop and grow, do not stop here. There are new things that can be found at the Kaklim Assembly this time.